Mental budgeting and the malleability of decision-making - Elgeka, Honey Wahyuni Sugiharto; Ma, Jianhong (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Financial difficulties commonly occur in college students' lives. Problems might be caused by a lack of understanding about managing money, such as falling into the temptation of buying unnecessary discounted goods or choice justification. The research aims to understand how mental budgeting influences purchasing discounted items and choice justification. In the study, two experiments were undertaken to explain the reaction of discount, and two others to describe choice justification (N=169 in Indonesia, N=168 in China). Mann-Whitney U and ANOVA tests were used to analyze the experiments. Mental budgeting scales were also employed in experiments 3 and 4. The results show that when individuals receive a discounted offer for luxury goods, they will fall into the temptation of buying them. This takes place because they do not want to lose the opportunity to obtain such goods at a cheap price. In addition, when individuals receive offers related to physiological needs (i.e., food), they will practice choice justification. This means that all people need to understand the concept of mental budgeting and make realistic budgets.